PENGARUH STRATEGI PEMBELAJARAN BERMEDIA INTERNET DAN MINAT BELAJAR SISWA TERHADAP HASIL BELAJAR KOGNITIF KETERAMPILAN KOMPUTER DAN PENGELOLAAN INFORMASI (KKPI) - Agusti NA; Samsudin NA (Akademika : Jurnal Teknologi Pendidikan, 2015)
This research objective is to find out the affect of learning strategies by using internet computer skill and information management (KKPI) in SMK Negeri 1 Sukabumi. There are four aspect being studied, namely (1) the achievement of student who use learning strategies by using internet media is better than those who use chart media; (2) there is interaction interest by using internet media during learning process is better than those who use chart media; (4) the achievement of students who use internet media is better than the student who use chart media with lower interest. This research used quantitative approach. The research data is the measurements of variable which was operated by using instrument. The instrument used in collecting data was the written test in the form of objectif test and interest test in likert scale.. Data collecting was conducted by using experimental method. The data analysis was conducted by using 2 rows ANOVA analysis with SPSS ver 20. The research result shows that : (1) there is a difference average score of learning result between students who use internet media and student who use chart media. The average score of students who use internet media is higher than their peers who use chart media (based on the calculation t is 2,252 > 2,021. This shows the achievement of students using internet media is better than those who use chart media). (2) There is influence of the interaction value sig is 0,033 < 0,05); (3) there is a difference on average score of learning result between students with high interest and students with lower interest. The average score of student with higher interest is higher than the average score of student with lower interest (based on calculation t is about 5,089 >2,101); (4) the affect of learning media toward learning achievement is significant for both students with higher interest and student with lower interest (based on calculation t count is,734 > 2,101) Based on those facts, teachers are supposed to be more creative in conducting learning process in order to create a comfortable and fun learning atmosphere. Teachers should also be more innovative in using learning media, particularly internet media. media. The headmaster should also pay more attention towards the fulfillment of learning media at school